Remote sensing of coastal environments - Wang, Yeqiao (Boca Raton, FL CRC Press, 2010)
"As coastal environments around the world continue to face unprecedented natural and anthropogenic threats, recent developments in the technologies that support geospatial data acquisition, imaging, and computing have profoundly enhanced monitoring capabilities in coastal studies. Providing systematic treatment of the key developments, Remote Sensing of Coastal Environments brings together renowned scholars to supply a clear presentation of the state-of-the-art in this technically complex arena. Edited by a recipient of the prestigious PECASE award, this book provides unrivaled coverage of the issues unique to coastal environments. It presents the best available data for measuring and monitoring coastal zones and explains how decision makers and resource managers can use this data to address contemporary issues in coastal zone management. The text illustrates the latest developments in active remote sensing, hyperspectral remote sensing, high spatial resolution remote sensing, the integration of remote sensing and in situ data, and covers the effects of land-cover and land-use change on coastal environments. Complete with representative case studies, this authoritative resource provides a timely snapshot of the wide range of remote sensing applications in coastal issues to enhance the understanding of how increasing disturbances to our coastal regions are affecting the ecological dynamics, biological diversity, and ecosystem health of our coastal environments. "--Publisher's description.
Remote sensing of coastal environments: an overview / Yeqiao Wang -- Interferometric synthetic aperture radar (InSAR) study of coastal wetlands over southeastern Louisiana / Zhong Lu and Oh-Ig Kwoun -- Mangrove canopy 3D structure and ecosystem productivity using active remote sensing / Marc Simard, Lola E. Fatoyinbo, and Naiara Pinto -- Integration of LiDAR and historical maps to measure coastal change on a variety of time and spatial scales / Cheryl J. Hapke -- Coastal 3D change pattern analysis using LiDAR series data / Guoqing Zhou -- Mapping the onset and progression of marsh dieback / Elijah Ramsey III and Amina Rangoonwala -- Estimating chlorophyll condition in southern New England coastal waters from hyperspectral aircraft remote sensing / Darryl J. Keith -- Mapping salt mash vegetation by integrating hyperspectral and LiDAR remote sensing / Jiansheng Yang and Francisco Artigas -- Mapping salt marsh in Jamaica Bay and terrestrial vegetation in Fire Island National Seashore using QuickBird satellite data / Yeqiao Wang, Mark Christiano, and Michael Traber -- Object-based data integration and classification for high-resolution coastal mapping / Jie Shan and Ejaz Hussain -- True-color digital orthophotography data for mapping coastal impervious surface areas / Yuyu Zhou and Yeqiao Wang -- FORMOSAT-2 images in mapping of South Asia tsunami disaster / Ming-Der Yang, Tung-Ching Su, and An-Ming Wu -- Remote sensing and in situ measurements for delineation and assessment of coastal marshes and their constituent species / Martha S. Gilmore ... [et al.] -- Quantifying biophysical conditions of herbaceous wetland vegetation in Poyang Lake of coastal China via multitemporal SAR imagery and in situ measurements / Limin Yang ... [et al.] -- EO-1 advanced land imager data in submerged aquatic vegetation mapping / Eric Akins, Yeqiao Wang, and Yuyu Zhou -- Remote sensing applications used to inventory and monitor natural resources in North Atlantic coastal National Parks / Sara Stevens and Courtney Schupp -- Coastal area land-cover change analysis for Connecticut / James D. Hurd ... [et al.] -- Effects of increasing urban impervious surface on hydrology of coastal Rhode Island watersheds / Yuyu Zhou ... [et al.] -- Contemporary land-use/land-cover change in coastal Pearl River Delta and its impact on regional climate / Limin Yang ... [et al.] -- Geospatial information for sustainable development: a case study in coastal East Africa / Yeqiao Wang ... [et al.]
Includes bibliographical references and index.
Keywords: Coastal ecology -- Remote sensing; Coasts -- Remote sensing; Coastal zone management -- Remote sensing; Environmental monitoring -- Remote sensing